Mapping possible interaction sites for crotoxin in CNF, a gamma PLA2 inhibitor from Crotalus durissus terrificus rattle snake, using SPOT synthesis - Campos, Patricia Cota; Oliveira, Hamine Cristina de [UNESP]; Ortolani, Paula Ladeira; Amaral de Melo, Lutiana; Fontes, Marcos R.M. [UNESP]; Fortes-Dias, Consuelo Latorre (Elsevier, 2023)
Phospholipases A2 (PLA2s) are main components of snake venoms. Several snake species possess endogenous PLA2 inhibitors in their circulating blood, which are generally known as sbPLIs (an acronym for snake blood phospholipase A2 inhibitors). The sbPLIs are categorized in three classes (alpha, beta or gamma) depending on the existence of distinguishing protein domains in their structure. The Crotalus durrissus terrificus venom has a highly neurotoxic PLA2 - crotoxin (CTX) - in its composition and the self-protection of the snake is mainly ensured by a sbγPLI named CNF (standing for Crotalus neutralizing factor). In an attempt to find smaller molecules able to inhibit the catalytic activity of CTX, in the present study we used linear peptide arrays to identify CNF segments possibly involved in the interaction with the toxin. Five reacting segments were identified as possible interacting regions. The target peptides were synthesized and located in the in silico CNF structure. Although all of them are exposed to the solvent, high concentrations were needed to inhibit the PLA2 activity of the whole venom or CTX. Limitations of the methodology employed and particular characteristics of CTX inhibition by CNF are discussed.
Keywords: CNF; Crotalus; Crotoxin; Phospholipase A2; Phospholipase A2 inhibitor; SPOT synthesis